MASTITE BOVINA: RELATO DE CASO - Lenhart, Daniel de Souza; Paulino, Greiciane Alves; Parise, Sabrina; Alves, Bruna Farias; Daneluz, Marina de Oliveira; Ansilieiro, Willian Jonas (Anais de Medicina Veterinária; v. 2 n. 1 (2022): 2022/2, 2022)
.